直动从动件圆柱凸轮变参CAD - 黄恺; 李雷 (Jixie chuandong)
The 3D parametric modeling of cylindrical cams is realized under Pro/E environment using its program function.As a result,the efficiency,accuracy,and extent of intelligence of design and manufacture for this type of cams can be improved significantly.